Changing clinical patterns and increasing prevalence in CADASIL. (19th May 2014) - Moreton, F. C.; Razvi, S. S. M.; Davidson, R.; Muir, K. W.
<x xml:space="preserve">Abstract</x> Objectives CADASIL is a monogenic small vessel vasculopathy causing recurrent stroke. Early descriptions suggested dementia and disability were common from the 5th decade but there is evidence of marked phenotypic variability. We investigated the prevalence and clinical features of CADASIL in the west of Scotland. Methods We undertook a retrospective review of clinical records of patients with confirmed CADASIL identified through a specialist clinic. Patients were divided to examine the effect of date of diagnosis on clinical outcomes and the characteristics at different ages. The location of pedigree members was used to estimate prevalence. Results Twenty‐one different CADASIL‐causing NOTCH3 mutations were identified in 49 pedigrees (61% in exon 4). Disease prevalence in Glasgow was 4.6/100, 000 adults. Mutation prevalence was estimated at 10.7/100, 000 population. Median age at first stroke in women (57 years) was higher than previous estimates, and stroke age in men was higher in patients diagnosed more recently (pre 2006 46 years, post 2006 56 years, P = 0.034). In patients over 58 years of age, 13/34 (38%) were living independently and 17/28 (61%) were mobile without aids when last seen. Conclusions CADASIL prevalence is at least 4.6 per 100, 000 adults. Median age of first stroke may be older than previously thought. Clinicians should consider CADASIL in the differential diagnosis even in older patients with stroke.